2022
DOI: 10.1186/s13034-022-00526-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term methylphenidate on social impairment in children with attention deficit/hyperactivity disorder: systematic review

Abstract: Attention Deficit/Hyperactivity disorder (ADHD) is one of the most common disorders in school-age children. In addition to learning difficulties associated with the disorder’s core symptoms of inattention and hyperactivity, children with ADHD display substantial social impairments. Methylphenidate (MPH) in formulations such as Ritalin or Concerta mitigates inattention and hyperactivity, but the effects of the therapy on social behavior in children with ADHD are not clear. This review aims to determine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 115 publications
0
3
0
2
Order By: Relevance
“…In relation to social competence and the effect of CNS medication, one systematic review found that children treated with medication and/or non-pharmacological interventions for their ADHD had better social functioning compared to untreated children with ADHD 58 . Other studies, however, have found that methylphenidate alone, or in combination with cognitive behavioral therapy, had only a limited effect on social behavior in children with ADHD 11 14 . In boys with ADHD, the positive effect of methylphenidate was specifically observed in higher compliance with expected behavior and a decrease in aggressive behavior tendencies 12 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In relation to social competence and the effect of CNS medication, one systematic review found that children treated with medication and/or non-pharmacological interventions for their ADHD had better social functioning compared to untreated children with ADHD 58 . Other studies, however, have found that methylphenidate alone, or in combination with cognitive behavioral therapy, had only a limited effect on social behavior in children with ADHD 11 14 . In boys with ADHD, the positive effect of methylphenidate was specifically observed in higher compliance with expected behavior and a decrease in aggressive behavior tendencies 12 .…”
Section: Discussionmentioning
confidence: 93%
“…Investigating the role of decision making in social problems in ADHD could lead to a complementary understanding compared to simply focusing on that inattentive, impulsive, and hyperactive people cannot focus, wait, or sit still enough to develop successful interactions. The core ADHD symptoms are in general found to predict social problems 10 , at the same time as, treatments that are effective in reducing ADHD symptoms, such as psychostimulant medication, only have small effects on enhancing social skills 11 14 . This suggests a dissociation between the core symptoms of ADHD and other neurocognitive processes linking the diagnosis to social impairment.…”
Section: Introductionmentioning
confidence: 99%
“…MPH is the first-line medication for this disorder and several works have studied the effect of the drug on different aspects of social performance. Alkalay and Dan ( Alkalay and Dan, 2022 ), after reviewing 15 studies on the impact of MPH on social performance in children between 6 and 14 years old with ADHD, concluded that MPH seems to improve the social deficit after weeks of treatment, increasing the capacity to recognize emotions and decreasing conflictive behaviors. However, as mentioned, these authors recognize that still controversial results exist and further studies are required to confirm conclusions.…”
Section: Psychostimulants and Social Behaviors In Humansmentioning
confidence: 99%
“…30 Es pertinente aclarar que existen niños que muestran otros síntomas no recogidos anteriormente en la descripción acotada ejemplo perretas, sobreprotección por algún miembro de la familia, donde pueden establecer prioridades entre hermanos y otros niños que forman parte del seno familiar, creando malestar entre ellos, suele aparecer egoísmo, comparaciones, susceptibilidad, pero no por ello, podemos afirmar que estamos en presencia de un trastorno de la conducta o del comportamiento, producto a que estas manifestaciones se aprecian de forma intermitente y transitorias, tienden a desaparecer con el tiempo o agudizarse de forma estable creando complejos de inferioridad, solo es un mal manejo de la situación dentro del seno familiar sin graves consecuencias, pero si no se le da el tratamiento adecuado pueden tener graves repercusiones negativas. 31 Las afectaciones que se producen en las relaciones interpersonales y en la esfera emocionalvolitiva, determinadas por una pobre e inadecuada formación de intereses, necesidades y principales motivaciones del educando, ligada a un insuficiente desarrollo de los sentimientos y a las diferentes alteraciones en los procesos cognoscitivos, permiten plantear que hay una repercusión importante en el aprendizaje escolar, el cual, en ocasiones por la torpeza que muestran los educandos, tiende a rendir por debajo de la norma. 32 Una de las causas que pueden desencadenar esta variedad de comportamientos es abandono del hogar de la figura materna o paterna, pérdida de un familiar allegado, violencia entre los integrantes de la familia, explotación por trabajo infantil, embarazo en la adolescencia, pueden sufrir crisis dentro del seno familiar por pasar su tutela o custodia o manos de otro miembro de la familia, cambios de domicilio y de escuela, rebeldía a la autoridad del adulto.…”
Section: Educandos Con Trastornos En El Comportamientounclassified
“…32 Una de las causas que pueden desencadenar esta variedad de comportamientos es abandono del hogar de la figura materna o paterna, pérdida de un familiar allegado, violencia entre los integrantes de la familia, explotación por trabajo infantil, embarazo en la adolescencia, pueden sufrir crisis dentro del seno familiar por pasar su tutela o custodia o manos de otro miembro de la familia, cambios de domicilio y de escuela, rebeldía a la autoridad del adulto. 31 Antes las manifestaciones antes mencionadas en ocasiones requieren asistencia en la especialidad de psiquiatría infantil, que apoyada en otras especialidades complementan el tratamiento medicamentoso si lo requiere, en busca de lograr un equilibrio emocional. Estos educandos son atendidos por la especialidad de logopedia, cuando requieren este servicio, en ocasiones solicitan ayuda especializada por sus propios medios, por no encontrar apoyo pertinente, por lo que se aprovecha el abanico de potencialidades que posea el educando para corregir y compensar sus alteraciones, con el apoyo docente educativo y asesoramiento especializado a las instituciones, encaminándolos de forma profiláctica hacia las actividades deportivas, culturales, trabajo en los talleres de distintas especialidades que tienen vínculo con la rama de la construcción, se fomentan el trabajo manual en aras de lograr la estabilidad emocional y se sientan las bases para el cuidado medioambiental mediante círculos de interés.…”
Section: Educandos Con Trastornos En El Comportamientounclassified